2018
DOI: 10.1002/vnl.21666
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polyhedral Oligomeric Silsesquioxanes Nanoparticles on Thermal and Mechanical Properties of Poly(vinyl chloride) Composite Materials

Abstract: The modification of poly(vinyl chloride) (PVC) by polyhedral silsesquioxane containing both methacryl and octyl groups (MeOctPOSS) was the task of studies. The PVC nanocomposites with MeOctPOSS concentration between 1 and 10 wt% were prepared by melt mixing processing, and the homogeneity of MeOctPOSS dispersion in the polymeric matrix was confirmed by scanning electron microscopy and energy dispersive spectroscopy observations. The influence of MeOctPOSS on glass transition temperature (Tg) determined by mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 38 publications
(72 reference statements)
1
15
0
Order By: Relevance
“…This effect results from reduced interactions between adjacent polymer chains induced by adding filler particles. The obtained results prove that the RRGED filler triggers slight PVC plasticisation [ 58 ]. Moreover, the DSC thermograms show an endothermic transition within the temperature range of 45 to 65 °C with a minimum at 54.5–56.1 °C.…”
Section: Resultsmentioning
confidence: 59%
“…This effect results from reduced interactions between adjacent polymer chains induced by adding filler particles. The obtained results prove that the RRGED filler triggers slight PVC plasticisation [ 58 ]. Moreover, the DSC thermograms show an endothermic transition within the temperature range of 45 to 65 °C with a minimum at 54.5–56.1 °C.…”
Section: Resultsmentioning
confidence: 59%
“…In the spectra of the PVC and PVC/GN shown in Fig. 3, bands at the wave numbers of 2941 cm − 1 and 1435 cm − 1 were observed, attributed to the presence of C-H bonds in the PVC macromolecule [25,27,39]. The peak at 1255 cm − 1 corresponds to bending vibrations of the C-H originating from CHCl [39].…”
Section: Ftir Spectroscopic Analysismentioning
confidence: 96%
“…Polymer composites are widely used in industrial applications due to their ability to combine the desired properties of various polymeric species. In particular, polyvinyl chloride (PVC) belongs to the most frequently used materials in the creation of nanocomposites because of its bene cial properties, such as its comparatively low cost, extensively developed processing, the possibilities of modi cation of its mechanical properties, and its high environmental resistance [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…There are also single notes on the utilization of thiol-ene [ 37 ], hydration [ 38 , 39 ] and click type reactions [ 40 , 41 , 42 ] for the synthesis of multifunctionalized silsesquioxanes. As stated, bifunctional SQ’s derivatives, due to the presence of different functionalities in the same core, possess a high application potential, e.g., as hydrophobic materials [ 43 , 44 , 45 , 46 ], mold material for nanoimprint lithography [ 47 ], anion sensors [ 31 , 48 ], Janus star polymers [ 49 , 50 ] or platforms for anchoring and delivering biologically active compounds in biomedicine [ 51 ]. Bifunctional silsesquioxanes with a T 8 R 4 R’ 4 formula are of particular scientific interest because it was demonstrated that they can be considered to be Janus-type molecules [ 52 ].…”
Section: Introductionmentioning
confidence: 99%